Laryngeal squamous cell papilloma is highly associated with human papillomavirus. (13th February 2018) - Orita, Yorihisa; Gion, Yuka; Tachibana, Tomoyasu; Ikegami, Kana; Marunaka, Hidenori; Makihara, Seiichiro; Yamashita, Yasuhiko; Miki, Kentaro; Makino, Takuma; Akisada, Naoki; Akagi, Yusuke; Kimura, Miyuki; et al.
Abstract : Human papillomavirus (HPV) infection is frequently associated with laryngeal squamous cell papilloma. HPV infection and p16-expression were associated with koilocytosis in laryngeal squamous cell papilloma. Abstract: Objective: To delineate the association between characteristics of adult-onset laryngeal squamous cell papilloma and human papillomavirus (HPV) infection. Methods: Clinical records and paraffin-embedded specimens of 77 papilloma patients who had been treated between 1998 and 2014 were collected. Of the 77 cases, 34 were identified in the larynx, 28 in the oral cavity and 15 in the oropharynx. Specimens were investigated by polymerase chain reaction (PCR) to detect HPV 6, 11, 16, 18, 31, 33, 35, 52b and 58, and immunohistochemical (IHC) staining for anti-p16 INK4a antibody. Results: In 21 cases (61.8%) with laryngeal squamous cell papilloma, various types of HPV were detected: 14 cases (41.2%) were positive of high-risk HPV, 18 (52.9%) were positive of low-risk HPV and 11 (32.4%) were positive of both high-risk HPV and low-risk HPV. Younger patients (<60 years) showed a higher rate of HPV infection than older patients. Among the 34 cases with laryngeal papilloma, no malignant transformation was observed during the study period. With IHC staining, positive expression of p16 was observed in 20 cases (58.8%). HPV infection and p16-expression were associated with the pathological finding of koilocytosis. Only four cases (14.3%) showed HPV-positivity in the oral cavity, and none of the 15 oropharyngeal cases were positive for HPV, and none of the oral cavity and oropharyngeal cases showed koilocytosis. Results of HPV-PCR and p16-IHC staining were significantly correlated each other. Conclusions: HPV infection is frequently associated with laryngeal squamous cell papilloma, and koilocytosis is a characteristic pathological finding. To the best of our knowledge, this is the first report which have described infections with multiple HPV types in laryngeal papilloma.